History of the immortality of the soul according to Commentaria De anima and Summa theologica by Suarez - Ñahuincopa-Arango, Antonio (2022)
This research work collects and analyzes valuable bibliographical information on the immortality of the soul in the Stagirite according to Suarez. Doctor Eximius’ breadth of knowledge on the history of philosophy is surprising, which serves as inspiration and support in his analysis of the sources, either directly or indirectly by reference to others. There are three indirect references: Eusebius of Caesarea, Augustinus Eugubinus and Augustinus Niphus. The sources of inspiration of the Spanish philosopher on the status quaestionis are thirty authors in total. Of them, sixteen authors are in favor of the mortality of the soul in Aristotle; eleven authors in favor of immortality in the Stagirite and three who maintain an ambiguous or doubtful position in Aristotle. Indeed, the thought of this cast of thinkers –from antiquity to the 16th century– cited by the Jesuit, really constitutes a history of the immortality of the human soul.